Pendekatan Diagnosis Berbasis Molekuler pada Pasien Talasemia - Bagus Pratama; Intanri Kurniati (Medula, 2019)
Thalassemia is a red blood disorder which is one of the causes of death and illness in Indonesia. This disease occurs due to genetic disorder that affect the inability of a person to synthesize globin chains. A globin chain is one of the constituents of hemoglobin so that abnormality of composition of hemoglobin will cause abnormality of elasticity and lysis of the erythrocytes. This disorder has various clinical manifestations ranging from anemia, pale, fatigue, pain, abnormalities in the bone (thalassemic facie) to jaundice and hepatosplenomegaly. Generally, the diagnosis of thalassemia uses a complete blood count including calculating the number of erythrocytes, hemoglobin levels, hematocrit levels, MCV and MCH, blood smear examination and hemoglobin electrophoresis. The genetic examination on molecular-based diagnostic approach is an examination to get a result of changes in gene sequences or genetic mutations that will affect the difference of clinical manifestation and severity of thalassemia patients. Molecular diagnosis can be made in an effort to improve the effective management and the quality of life of patients.